PSYCHOLOGICAL WELL BEING OF GIRLS WHO MARRIED EARLY BECAUSE OF POVERTY - Isabella Marsha; Nicholas Indra Nurpatria (Faculty of Psychology, Atma Jaya Catholic University of Indonesia, 2018)
This research is aimed to examine the psychological well being of girls who married early because of poverty. Ryff theory is used to understand how self acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, personal growth will contribute or otherwise restrain the psychological well being of those early married young women. This study used a qualitative method by interviewed 3 girls in Tambora-West Jakarta aged 16-17 years who married early because of poverty, have been married for 5-8 years, low income families (lived in densely populated residential house with their parents, has no own income, and husband’s income under three million a month). The results showed that 3 participants accept their selves include strenghts and weaknesses. They have a positive relationship with others by maintain communication and helped others. Three participants only have autonomy in domestic area, can balance daily activities related to domestic work. Only one participant consistent adjust her environment according to her needs, that is work at home to earn money. They have same life purpose, that is be a good housewife and have their own house, although obstructed in the achievement of material goals. Personal growth of three participants visible on domestic capability. Supporting factors of their psychological well being are social support from family and husband, self awareness of being wife and mother, and also life experience. Inhibit factors of their psychological well being are difficult economic conditions, domination of husband role which governs life of participants, also role and responsibility as a wife. In this study, found that girls who married early have a good psychological well being even though the economy is still difficult because they are in a supportive environment. This research is aimed to examine the psychological well being of girls who married early because of poverty. Ryff theory is used to understand how self acceptance, positive relations with others, autonomy, environmental mastery, purpose in life, personal growth will contribute or otherwise restrain the psychological well being of those early married young women. This study used a qualitative method by interviewed 3 girls in Tambora-West Jakarta aged 16-17 years who married early because of poverty, have been married for 5-8 years, low income families (lived in densely populated residential house with their parents, has no own income, and husband’s income under three million a month). The results showed that 3 participants accept their selves include strenghts and weaknesses. They have a positive relationship with others by maintain communication and helped others. Three participants only have autonomy in domestic area, can balance daily activities related to domestic work. Only one participant consistent adjust her environment according to her needs, that is work at home to earn money. They have same life purpose, that is be a good housewife and have their own house, although obstructed in the achievement of material goals. Personal growth of three participants visible on domestic capability. Supporting factors of their psychological well being are social support from family and husband, self awareness of being wife and mother, and also life experience. Inhibit factors of their psychological well being are difficult economic conditions, domination of husband role which governs life of participants, also role and responsibility as a wife. In this study, found that girls who married early have a good psychological well being even though the economy is still difficult because they are in a supportive environment. Keywords: psychological well being, girls, early marriage, poverty